Influence of Family Communication and Family Self-Concept on Life Satisfaction in University Students from Juliaca - Phala Turpo, Samuel (2026)
To determine the degree of influence of family communication and family self-concept on life satisfaction in university students from the city of Juliaca. A cross-sectional predictive design and non-probabilistic sampling were used. The sample consisted of 823 university students. It used Family Communication Scale (FCS), AF5 Self-Concept Scale, and School Satisfaction Scale (EBSE). Show that the proposed model had a good fit 2 (186) = 781.8, p < .001, CFI = .974, RMSEA = .062, SRMR = .040, evidencing that family communication and family self-concept influence on life satisfaction. It is concluded that family communication and self-concept influence on life satisfaction in university students.